1978
DOI: 10.1113/jphysiol.1978.sp012487
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of uptake1 and uptake2 in terminating the cardiovascular activity of noradrenaline in normotensive and genetically hypertensive rats.

Abstract: SUMMARY1. In pithed, pancuronium-treated rats, inhibition of Uptake, with desmethylimipramine (2.5 mg/kg i.v.) increased the time course of the pressor response to vasomotor nerve stimulation (1 and 5 Hz for 5 sec) but not the time course of the pressor response to injected noradrenaline (10 and 50 ng i.v. 6. This defect may be related to the high resting heart rate and abnormal cardiac catecholamine turnover observed to exist in the Otago hypertensive rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Acute adrenalectomy has also been shown to suppress, markedly, the secondary component of biphasic pressor response to spinal cord stimulation in pithed rats (Flavahan et al 1985;Tsujimoto et al 1987). By contrast, however, it has been reported that pressor responses to spinal cord stimulation (Bell & Kushinsky 1978) and to locus coeruleus stimulation (Drolet & Gauthier 1987) after acute surgical adrenalectomy remained comparable with those observed before adrenalectomy. It has also been shown that adrenal demedullation had little effect on the overall pressor response to reflex stimulation or to direct spinal cord stimulation (Yamaguchi & Kopin 1979;Sakaguchi et al 1983).…”
Section: Discussionmentioning
confidence: 85%
“…Acute adrenalectomy has also been shown to suppress, markedly, the secondary component of biphasic pressor response to spinal cord stimulation in pithed rats (Flavahan et al 1985;Tsujimoto et al 1987). By contrast, however, it has been reported that pressor responses to spinal cord stimulation (Bell & Kushinsky 1978) and to locus coeruleus stimulation (Drolet & Gauthier 1987) after acute surgical adrenalectomy remained comparable with those observed before adrenalectomy. It has also been shown that adrenal demedullation had little effect on the overall pressor response to reflex stimulation or to direct spinal cord stimulation (Yamaguchi & Kopin 1979;Sakaguchi et al 1983).…”
Section: Discussionmentioning
confidence: 85%
“…Hermsmeyer (1976) has proposed that it is the increased K-and Na-permeability which is indirectly the cause of the increased noradrenaline sensitivity. The resting membrane potential of the SHR and WKY cells is the same (Hermsmeyer, 1976;Bell & Kushinsky, 1978). Therefore an increased K-and Na-permeability might be expected to cause or require an increased Na-K electrogenic pump activity in the SHR cells, and there is now experimental evidence for such an increased activity (Hermsmeyer, 1976;Webb & Bohr, 1979).…”
Section: Calcium Activationmentioning
confidence: 94%
“…Previous studies have failed to demonstrate significant vascular effects following stimulation of the adrenal medulla (Celander, 1954;Bell & Kushinsky, 1978;Yamaguchi & Kopin, 1979;Docherty, 1979), suggesting that extra-synaptic or 'hormonal' (Ariens & Simonis, 1976) receptor sites may have a limited role in cardiovascular regulation (see also , Neil, 1975;Lewis, 1975). The aim of the present study was to investigate the vascular effects evoked by sympathoadrenal stimulation in the pithed rat in order to determine which populations of postjunctional adrenoceptors might be activated, under physiological conditions, by the sympathetic nervous system and whether these could account for all of the response.…”
Section: Introductionmentioning
confidence: 99%